RNAi-based small molecule repositioning reveals clinically approved urea-based kinase inhibitors as broadly active antivirals. - Markus Lesch; Madlen Luckner; Michael Meyer; Friderike Weege; Isabella Gravenstein; Martin Raftery; Christian Sieben; Laura Martin-Sancho; Aki Imai-Matsushima; Robert-William Welke; Rebecca Frise; Wendy Barclay; et al. (PLoS Pathogens, 2019)
Influenza viruses (IVs) tend to rapidly develop resistance to virus-directed vaccines and common antivirals targeting pathogen determinants, but novel host-directed approaches might preclude resistance development. To identify the most promising cellular targets for a host-directed approach against influenza, we performed a comparative small interfering RNA (siRNA) loss-of-function screen of IV replication in A549 cells. Analysis of four different IV strains including a highly pathogenic avian H5N1 strain, an influenza B virus (IBV) and two human influenza A viruses (IAVs) revealed 133 genes required by all four IV strains. According to gene enrichment analyses, these strain-independent host genes were particularly enriched for nucleocytoplasmic trafficking. In addition, 360 strain-specific genes were identified with distinct patterns of usage for IAVs versus IBV and human versus avian IVs. The strain-independent host genes served to define 43 experimental and otherwise clinically approved drugs, targeting reportedly fourteen of the encoded host factors. Amongst the approved drugs, the urea-based kinase inhibitors (UBKIs) regorafenib and sorafenib exhibited a superior therapeutic window of high IV antiviral activity and low cytotoxicity. Both UBKIs appeared to block a cell signaling pathway involved in IV replication after internalization, yet prior to vRNP uncoating. Interestingly, both compounds were active also against unrelated viruses including cowpox virus (CPXV), hantavirus (HTV), herpes simplex virus 1 (HSV1) and vesicular stomatitis virus (VSV) and showed antiviral efficacy in human primary respiratory cells. An in vitro resistance development analysis for regorafenib failed to detect IV resistance development against this drug. Taken together, the otherwise clinically approved UBKIs regorafenib and sorafenib possess high and broad-spectrum antiviral activity along with substantial robustness against resistance development and thus constitute attractive host-directed drug candidates against a range of viral infections including influenza.